Divergent transcriptomic signatures in response to salinity exposure in two populations of an estuarine fish - Jeffries, Ken M. (Evol Appl, 2019)
In estuary and coastal systems, human demand for freshwater, climate change‐driven precipitation variability, and extreme weather impact salinity levels, reducing connectivity between mesohaline coastal fish populations and potentially contributing to genomic divergence. We examined gill transcriptome responses to salinity in wild‐caught juveniles from two populations of Sacramento splittail (Pogonichthys macrolepidotus), a species of conservation concern that is endemic to the San Francisco Estuary, USA, and the lower reaches of its tributaries. Recent extreme droughts have led to salinities above the tolerance limits for this species, creating a migration barrier between these populations, which potentially contributed to population divergence. We identified transcripts involved in a conserved response to salinity; however, the more salinity‐tolerant San Pablo population had greater transcriptome plasticity (3.6‐fold more transcripts responded than the Central Valley population) and a response consistent with gill remodeling after 168 hr of exposure to elevated salinity. The reorganization of the gill in response to changing osmotic gradients is a process critical for acclimation and would facilitate enhanced salinity tolerance. We detected an upregulation of receptors that control the Wnt (wingless‐type) cell signaling pathway that may be required for an adaptive response to increases in salinity, patterns not observed in the relatively salinity‐sensitive Central Valley population. We detected 62 single nucleotide polymorphisms (SNPs) in coding regions of 26 transcripts that differed between the populations. Eight transcripts that contained SNPs were associated with immune responses, highlighting the importance of diversity in immune gene sequences as a defining characteristic of genomic divergence between these populations. Our data demonstrate that these populations have divergent transcriptomic responses to salinity, which is consistent with observed physiological differences in salinity tolerance.